THE ROLE OF THE CLINICAL PHARMACIST IN THE SELECTION OF NON-STEROIDAL ANTI-INFLAMMATORY DRUGS FOR THE PATIENT - Tamaz Tchumburidze; Nino Nemsitsveridze; Ketevan Pachkoria; Ioseb Tomadze; Lizi Tomadze (Theoretical Hypotheses and Empirical Results, 2023)
Nonsteroidal anti-inflammatory drugs belong to one of the most common groups of drugs that are widely used in medicine. Their positive properties are: - suppressing inflammation, relieving pain, reducing fever. However, they are characterized by adverse reactions: gastropathies, damage to the cardiovascular system, myocardial infarction, stroke, negative impact on articular cartilage, adverse effects on liver and kidney functions, exacerbation of bronchial asthma and bronchial disease, etc. Therefore, the age of the patient and accompanying diseases should be taken into account when prescribing the drug. In the process of implementing pharmaceutical care, the clinical pharmacist should be well versed not only in pharmaceutical factors, but also in medical issues when selecting non-steroidal anti-inflammatory drugs. In the process of providing care, the clinical pharmacist should find out the risk factors of the patient's condition based on the survey and refer the patient to the doctor if dangerous symptoms are detected. Therefore, a detailed study of pharmaceutical care in those patients for whom the pharmacist should choose AAS is a very urgent problem.